An Epidemiological Study and the Effect of Motivational Enhancement Therapy ‎Among Medical Students Having Internet Addiction - Anurag , Kirti; Dash, Lagnajit; Mahapatra , Hiranmaya; Senapati , Rupesh; Dash , Nirlipta; Kar, Dattatreya (International Journal of Basic and Applied Sciences, 2025)
Internet addiction has been defined as a severe preoccupation, urges, or behaviours to use the internet, causing distress. Psychiatric comorbidities ‎associated are impulse control disorders, anxiety, depression, and overconsumption of pornographic materials. Some psychosocial ‎interventions have been applied, but no uniform guideline has been formulated to date. Motivational enhancement therapy has proved to be ‎an extremely efficient technique in curbing internet addiction. The study was a cross-sectional study subjects were selected through purposive sampling. Internet addiction test, Smartphone addiction scale, and general health questionnaires were used to screen the students. Pre-assessment was done to find out the associated psychopathology with internet addiction, and suspected cases of moderate to severe internet ‎addiction group were taken for further intervention using MET, followed by post-assessment. Among subjects who used internet for >2years ‎‎15.6% had high risk of smart phone addiction, 30.8% had smart phone addiction, 12.4% had moderate internet addiction and 3.6% had ‎severe internet addiction which was far more higher than subjects using internet for lesser duration It was evident that the scores of partici-‎pants on the scales of IAT, SAS and GHQ28 before and after MET had significantly reduced. This tells us that MET has a significant effect ‎in reducing moderate to severe internet addiction, leading to a decrease in distress. Smartphone addiction goes hand in hand with internet ‎addiction, so they both should be addressed together. MET is an effective modality of therapy for internet addiction, but more detailed studies ‎are needed to understand the intricacies of it‎.